Analisis Penanganan Manipulasi Transfer Pricing Perpajakan Dalam Menjawab Tantangan Global - Dewi, Renita Rachma; Mustikasari, Elia (E-Jurnal Akuntansi, 2020)
Transfer pricing basically aims to measure company performance and has become a media to manipulate taxes, resulting in state revenue, which results in state stability, national problems and global challenges. This research method is qualitative with the transfer pricing case study approach. The data is secondary and the process of collecting data from reliable online sources. The analysis technique uses data reduction, data display and verification. The results explain that the factors of manipulation of transfer pricing are the presence of special company relationships, bonus systems and mechanisms, acquisition of unnatural profits, foreign ownership and political cost. The process of handling is reforming taxation, which includes natural resources, organizations, business processes, data, information technology and regulation. The role of behavioral accounting is to create professionalism and responsibility with the principles of fairness and custom of business, value chain analysis, activity based costing and just in time philosophy. Keywords: Transfer Pricing; Tax; Behavioral Accounting; Global Challenges.